A comparative assessment of proposed offshore wind power demonstration projects in the United States. (November 2015) - Bates, Alison; Firestone, Jeremy
Abstract: Wind energy development on land has faced local opposition for reasons such as effects on cultural landscapes and wildlife, which can be instrumental in whether or not and the speed with which a project moves toward completion. Offshore wind can generate electricity where onshore wind is limited. Factors leading to support for, or opposition to, offshore wind energy are not well known, particularly for developments that are near-shore and in-view of coastal communities. Here we present results from a survey of 699 residents (35.5% response rate) completed in 2013 in greater Atlantic City, New Jersey and coastal Delaware, United States, where near-shore wind demonstration projects had been proposed. We examined how the public considers the societal tradeoffs that are made to develop small-scale, in-view demonstration wind projects instead of larger facilities farther offshore. Results indicate that a strong majority of the public supports near-shore demonstration wind projects. We find the primary reasons for support include benefits to wildlife, cost of electricity, and job creation, while the primary reasons for opposition include wildlife impacts, aesthetics, tourism, and user conflicts. These factors differ between the two communities and highlight the importance of local, community engagement in the early stages of development.